An exploratory survey study of disorder and its association with safety culture in four hospitals - Kate Churruca; Louise A. Ellis; Janet C. Long; Chiara Pomare; Winston Liauw; Caroline M. O'Donnell; Jeffrey Braithwaite (BMC, 2022)
Abstract Background Signs of disorder in neighbourhoods (e.g., litter, graffiti) are thought to influence the behaviour of residents, potentially leading to violations of rules and petty criminal behaviour. Recently, these premises have been applied to the hospital context, with physical and social disorder found to have a negative association with patient safety. Building on these results, the present study investigates whether physical and social disorder differ between hospitals, and their relationship to safety culture. Methods We conducted a cross sectional survey with Likert-style and open response questions administered in four Australian hospitals. All staff were invited to participate in the pilot study from May to September 2018. An analysis of variance (ANOVA) was used to examine differences in disorder by hospital, and hierarchical linear regression assessed the relationship of physical and social disorder to key aspects of safety culture (safety climate, teamwork climate). Open responses were analysed using thematic analysis to elaborate on manifestations of hospital disorder. Results There were 415 survey respondents. Significant differences were found in perceptions of physical disorder across the four hospitals. There were no significant differences between hospitals in levels of social disorder. Social disorder had a significant negative relationship with safety and teamwork climate, and physical disorder significantly predicted a poorer teamwork climate. We identified five themes relevant to physical disorder and four for social disorder from participants' open responses; the preponderance of these themes across hospitals supported quantitative results. Conclusions Findings indicate that physical and social disorder are important to consider in attempting to holistically understand a hospital's safety culture. Interventions that target aspects of physical and social disorder in a hospital may hold value in improving safety culture and patient safety.